2022
DOI: 10.1038/s41467-022-34062-6
|View full text |Cite|
|
Sign up to set email alerts
|

Deciphering the atomic-scale structural origin for large dynamic electromechanical response in lead-free Bi0.5Na0.5TiO3-based relaxor ferroelectrics

Abstract: Despite the extraordinary electromechanical properties of relaxor ferroelectrics, correlating their properties to underlying atomic-scale structures remains a decisive challenge for these “mess” systems. Here, taking the lead-free relaxor ferroelectric Bi0.5Na0.5TiO3-based system as an example, we decipher the atomic-scale structure and its relationship to the polar structure evolution and large dynamic electromechanical response, using the direct atomic-scale point-by-point correlation analysis. With judiciou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…, Bi-displacement along the 〈111〉 c is suppressed, and associated local structural heterogeneity is decreased. Yin et al 74 using first-principles calculation reported that there is a small energy gap, Δ E ≈ 16.7 meV, between [111] c and [001] c displacement directions of Bi 3+ cation. The more homogeneous distribution or more ordered A-site cation arrangement due to the quenching can be further rationalized from the fact that a significant increase in tetragonal distortion and domain wall density was observed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…, Bi-displacement along the 〈111〉 c is suppressed, and associated local structural heterogeneity is decreased. Yin et al 74 using first-principles calculation reported that there is a small energy gap, Δ E ≈ 16.7 meV, between [111] c and [001] c displacement directions of Bi 3+ cation. The more homogeneous distribution or more ordered A-site cation arrangement due to the quenching can be further rationalized from the fact that a significant increase in tetragonal distortion and domain wall density was observed.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of thermal quenching of KBT from 900 °C, a more homogeneous distribution (less clustering) of Bi 3+ is established as quenching from high temperature did not provide the time necessary to form a signicant degree of the Bi 3+ -rich clusters, i.e., Bidisplacement along the h111i c is suppressed, and associated local structural heterogeneity is decreased. Yin et al 74 using rst-principles calculation reported that there is a small energy gap, DE z 16.7 meV, between [111] quenching can be further rationalized from the fact that a signicant increase in tetragonal distortion and domain wall density was observed. Previous works have reported the relation between increased tetragonal distortion and increased local Asite cation ordering in KBT by PDF analysis and DFT calculation.…”
Section: Temperature-dependent Piezoelectric Propertiesmentioning
confidence: 99%
“…In addition, due to the toxicity of Pb, environmentally benign lead-free piezoelectrics have received intensive attention, such as BaTiO 3 [ 39 , 40 , 41 ], sodium bismuth titanate (BNT) [ 42 , 43 , 44 ], and potassium sodium niobate (KNN) [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. In Figure 2 b, Jong et al demonstrated a BaTiO 3 hybrid film by adopting a simple and facile inkjet-printing process [ 53 ].…”
Section: Piezoelectric Materialsmentioning
confidence: 99%
“…Unlike the typical (Na 0.5 Bi 0.5 )­TiO 3 (NBT) matrix with strong FE properties, which is often used to form RFEs, (Na 0.5 Bi 0.5 ) 0.7 Sr 0.3 TiO 3 (NBST) doped with 30 mol % Sr 2+ ions at the A-site of NBT has been widely studied for its equally large P m of 47.2 μC/cm 2 but lower P r of 8.2 μC/cm 2 . However, the W rec of NBST is too low to meet the application requirements owing to premature polarization saturation, and so much effort has been made to improve its W rec by introducing Bi­(Mg 2/3 Nb 1/3 )­O 3 , Bi­(Ni 0.5 Sn 0.5 )­O 3 , and Sr­(Ti 0.85 Zr 0.15 )­O 3 .…”
Section: Introductionmentioning
confidence: 99%